Investigation of Adsorption Isotherms of 2-Naphthol on Carbon Nanotube - Vadi, Mahdi; Saybankhirabadi, Fatemeh (Asian Journal of Chemistry, 2011)
This paper has studied equilibrium adsorption isotherms of 2-naphthol on carbon nanotube. And also results of experiments through Freundlich, Temkin and Langmuir models have been studied and it has found different parameters of these models for carbon nano-tube absorbent. According to the error rate for each model, we abstained a good agreement between these data which it showed the best agreement by Freundlich model. With the spectrophotometer (UV/ VIS) the adsorption diagram was obtained based on wavelength for 2-naphthol. Experimental result showed that by increasing concentrations of 2-naphthol therefore adsorption rate will increase too. The highest adsorption rate is for 6 ppm concentration of 2-naphthol.